The Semantic Comprehension of Persian Endocentric and Exocentric Compounds in non-Persian Speakers - Montazeri, Sara; Afkhami, Ali; Kamyabi Gol, Atiyeh (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
Semantic comprehension of Persian compound nouns in non-Persian speakers of TPSL department was investigated using a cognitive-semantics approach. Regarding the semantic relationships between the bases of compound nouns, two were selected based on presence or lack of semantic head. Then, sufficient data were collected from different texts through a desk research method to make a frequency dictionary of endocentric and exocentric compound nouns based on the knowledge level of students. A definition-word pairing test was then selected and most frequent compound nouns (24 compound nouns) were identified and used for the test, developed and run in the form of an application for smart phones by an application developer and participants were provided with it. Overall, 888 data were collected from the test results and analyzed using standard statistical tests suggesting that due to presence of semantic head in endocentric compounds, speed and level of comprehending them was higher than exocentric compounds; moreover, a correlational relationship between comprehension of these compounds was identified. Therefore, the relationship between components of endocentric compounds was understood faster than exocentric compounds. Thus, applicability of CARIN theory was verified.